Cost-benefit analysis of Nigeria’s continued role in ECOWAS - Tijjani, Chubado Babbi; Ozden, Kemal (Journal of Management, Economics, and Industrial Organization, 2021)
This study attempts to discuss the cost-benefit analysis of Nigeria’s continued membership in the Economic Community of West African States (ECOWAS). The study identifies the issues belabouring the relationship between Nigeria and ECOWAS and it concludes that Nigeria can only remain in ECOWAS if the relationship promotes the national interest of the Nigerian populace. This article studied the structure, organisation, function, aims, and objectives of ECOWAS alongside Nigeria’s achievement and contributions to ECOWAS. The paper discussed the cost and benefit of Nigeria’s continued membership of ECOWAS and recommended a revision of the relationship that presently exists between Nigeria and ECOWAS. The paper posited that the principles of quid pro quo must be adopted in Nigeria’s relationship with ECOWAS.